Financial impact of risk on municipal earnings (2007)
To evaluate the relation between regional earnings and risk across the US economy, this article uses a heteroscedastic model that captures earnings uncertainty. We then implement a nonlinear estimator that simultaneously estimates the variance of the econometric residual and the effect of the variance on expected earnings. Estimation results show the association between risk and earnings for local economies.